1972
DOI: 10.3171/jns.1972.37.3.0280
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary apoplexy: a review and reappraisal

Abstract: ✓ The authors report their experience with nine cases of acute pituitary apoplexy; eight had proven chromophobe adenomas, and two of these patients had the clinical stigmata of Cushing's syndrome. One patient who displayed acromegalic features was treated with x-ray, and no pathological specimen was obtained. The outstanding clinical features of acute pituitary apoplexy were sudden headache, depressed consciousness, ophthalmoplegia, meningismus, and signs of compression of the optic nerve or chiasma. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
101
0
3

Year Published

1974
1974
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(104 citation statements)
references
References 31 publications
0
101
0
3
Order By: Relevance
“…Suggested possibilities include ischemia of the tumor, as a result of outgrowing its blood supply 5,6,13,16) ; kinking of the superior hypophyseal artery against the diaphragm sellae; or the presence of vasculopathy or abnormal blood vessels, with a tendency to hemorrhage 5) . In our study, there were 14 (43.8%) pituitary apoplexy patients with a volume under 1 mL; the majority of them (11 patients, 34.4%) were categorized as being in group I, In small-size apoplexy, Robit and Fein 17) suggest that the trabecular arteries arising from the superior hypophyseal artery may be compressed by the diaphragm sellae, thereby causing ischemia and secondary necrosis of the tumor. Presumably, however, the mass was insufficient to compress the surrounding parasellar structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested possibilities include ischemia of the tumor, as a result of outgrowing its blood supply 5,6,13,16) ; kinking of the superior hypophyseal artery against the diaphragm sellae; or the presence of vasculopathy or abnormal blood vessels, with a tendency to hemorrhage 5) . In our study, there were 14 (43.8%) pituitary apoplexy patients with a volume under 1 mL; the majority of them (11 patients, 34.4%) were categorized as being in group I, In small-size apoplexy, Robit and Fein 17) suggest that the trabecular arteries arising from the superior hypophyseal artery may be compressed by the diaphragm sellae, thereby causing ischemia and secondary necrosis of the tumor. Presumably, however, the mass was insufficient to compress the surrounding parasellar structure.…”
Section: Discussionmentioning
confidence: 99%
“…Signal intensity changes occur in subacute hemorrhage due to the degradation of hemoglobin into methemoglobin; in such cases the signal should appear bright on both T1-WI and T2-WI 3,10) . In the chronic phase (i.e., over 15 days), sedimentation of blood products may create a fluid level within the mass-a feature that is highly suggestive of hemorrhagic pituitary apoplexy 3,8,14,17) . In our study, we found that preoperative findings of pituitary hemorrhage on the MRI sequences correlated well with clinical symptoms and operative findings.…”
Section: Discussionmentioning
confidence: 99%
“…28 It also occurs silently without production of symptoms, as shown by histological features consistent with apoplexy in as many as 25% of microadenomas removed surgically. 24,37 Previously proposed mechanisms for pituitary apoplexy include reduced blood supply to the tumor produced by events such as hypotension, rapid growth outpacing the development of adequate blood supply to the tumor, 12 direct pressure by the tumor on the portal vessels or the hypophyseal arteries causing acute ischemia of the tumor, 32 increased intratumoral pressure which itself acutely impairs the blood flow to the tumor, 47 increased metabolic activity beyond adequate arterial supply after stimulation with hypothalamic releasing factors, 31 and hemorrhage resulting from fragility of the tumor vessels. 10 There is evidence supporting these proposed mechanisms as contributing factors in acute pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical entity was described relatively late, in 1950, by Brougham et al 12 Since then pituitary apoplexy has been the subject of many reports describing the clinical presentation, patient management, imaging features, and outcome, as well as reports of acute circumstances predisposing to its occurrence. 9,10,14,15,17,[22][23][24][25]29,32,36,37,39,45 We propose here that infarction of these tumors is the product of a combination of intrinsic features of these tumors and that it is the tenuous imbalance between their high rate of demand for nutrients combined with their limited intrinsic blood supply that makes them vulnerable to infarction, with or without precipitating events, and suggest that this circumstance may permit new approaches to treatment based on this peculiar vulnerability. …”
mentioning
confidence: 99%
“…6 ). A fisiopatologia da apoplexia pituitária pode envolver a compressão de artérias trabeculares pelo diafragma selar com isquemia primária e posterior necrose tumoral 7 . Isto porém, não é aplicável a todos os casos, principalmente nos microadenomas e adenomas intraselares.…”
Section: Pituitary Apoplexy Followed By Endocrine Remission: Report Ounclassified